Dual Agonist of Farnesoid X Receptor and Takeda G Protein‐Coupled Receptor 5 Inhibits Hepatitis B Virus Infection In Vitro and In Vivo. Issue 1 (15th June 2021) - Ito, Kiyoaki; Okumura, Akinori; Takeuchi, Junko S.; Watashi, Koichi; Inoue, Rieko; Yamauchi, Taeko; Sakamoto, Kazumasa; Yamashita, Yukiko; Iguchi, Yusuke; Une, Mizuho; Wakita, Takaji; Umezawa, Kazuo; et al.
Abstract : Background and Aims: Chronic HBV infection is a major health problem worldwide. Currently, the first‐line treatment for HBV is nucleos(t)ide analogs or interferons; however, efficient therapeutic approaches that enable cure are lacking. Therefore, anti‐HBV agents with mechanisms distinct from those of current drugs are needed. Sodium taurocholate cotransporting polypeptide (NTCP) was previously identified as an HBV receptor that is inhibited by several compounds. Farnesoid X receptor (FXR) activation also inhibits NTCP function. Approach and Results: In this study, we investigated the inhibitory effect of bile acid (BA) derivatives—namely obeticholic acid (OCA), 6α‐ethyl‐24‐nor‐5β‐cholane‐3α, 7α, 23‐triol‐23 sulfate sodium salt (INT‐767; a dual agonist of FXR and Takeda G protein‐coupled receptor [TGR5]), and 6α‐ethyl‐23(S)‐methyl‐cholic acid (INT‐777; a TGR5 agonist)—3‐(2, 6‐dichlorophenyl)‐4‐(3′‐carboxy‐2‐chlorostilben‐4‐yl)oxymethyl‐5‐isopropylisoxazole (GW4064; a FXR agonist), cyclosporin A, and irbesartan. OCA and INT‐777 suppressed HBV infection in HepG2‐human NTCP‐C4 cells. Interestingly, INT‐767 showed potent inhibition by attaching to HBV particles rather than binding to NTCP. As an entry inhibitor, INT‐767 was stronger than various natural BAs. Furthermore, in chimeric mice with humanized liver, INT‐767 markedly delayed the initial rise of HBsAg, HBeAg, and HBV DNA and reduced covalently closed circular DNA. The strong inhibitory effect of INT‐767 may be due to the cumulative effect of its ability to inhibit the entry of HBV and to stimulate FXR downstream signaling, which affects the postentry step. Conclusions: Our results suggest that BA derivatives, particularly INT‐767, are prospective candidate anti‐HBV agents. Clarifying the underlying mechanisms of BA derivatives would facilitate the development of anti‐HBV agents.